PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. DUNKINDO LESTARI CABANG KALIMALANG - Lira Ariestin; Prawoto (Human Capital Development, 2017)
Purpose- To find out the effect of leadership and compensation on employee performance in. dunkindo lestari branch of kalimalang. Design/methodology/approach- In this study, the authors conducted a survey by distributing questionnaires to employees of PT.Dunkindo Lestari Kalimalang Branch. The number of samples to this research is as many as 100 employees obtained by non-random sampling technique coincidence, in which respondents who are samples are employees who are willing to fill out a questionnaire. After doing the questionnaire. For descriptive analysis method, writer use percentage analysis and mean. To test the influence of leadership and compensation, the author uses linear regression analysis with the test d and F test. Findings- The results of the research show the two variables together affect employee performance in PT.Dunkindo Lestari Kalimalang Branch. By using t test, it is found that leadership give significant influence to the improvement of employee performance at PT.Dunkindo Lestari Kalimalang Branch is15.27%, while compensation also affect to employee performance at PT.Dunkindo Lestari Kalimalang Branch. The ability of the 11.77% compensation variable to explain the performance diversity is 37.5%. If both variables simultaneously found the ability of both variables to explain the diversity of performance is 37.5%, other factors of 62.5% are not discussed in this study, such as work environment, human resource quality, organizational culture, corporate governance, competencies, rewards and factors others that are not discussed by researchers.